Mystique marriage of the chaman and animism among the ashaninka of Eastern Peru - Rojas Zolezzi, Enrique (2019)
This article explains the place of the chaman in the animistic cosmological system of the ashaninka. Since his marriage with the spirit of the tobacco he is able to repair the relations between humans, and humans with not humans.